Do plant biostimulants affect the survival of Escherichia coli in lettuce? - Fiore, Leonardo; Cardarelli, Mariateresa; Ruzzi, Maurizio; Ficca, Anna Grazia; Rouphael, Youssef; Luziatelli, Francesca; Colla, Giuseppe (Frontiers in Plant Science, 2024)
IntroductionConsidering that plant biostimulants can be sprayed multiple times on leafy crops even just before harvest, it is relevant to know the impact of biostimulant applications on Escherichia coli population dynamics of lettuce leaves to ensure food safety. Two trials were carried out to investigate whether the applications of a seaweed extract and a vegetal-derived protein hydrolysate (PH) could affect the E. coli growth in shake flasks (Exp. 1) and plant growth and survival of artificially inoculated E. coli on the leaf surface of lettuce grown in a floating system (Exp. 2).MethodsThe non-pathogenic E. coli strain K12 was used in both trials. In Exp. 1, biostimulants’ inhibitory/stimulatory effect on E. coli growth was evaluated in liquid culture after 24 hours of incubation at 37°C. The 31-day agronomic trial (Exp. 2) was conducted in a polyethylene greenhouse on lettuce grown in a floating system.ResultsIn Exp. 1, E. coli growth was not affected by LB medium amended with biostimulants, whereas both biostimulants stimulated total aerobic bacteria and inhibited E. coli population on lettuce leaves with a more pronounced inhibitory effect of PH applications on E. coli (Exp. 2). Total plant biomass and its partitioning (on fresh and dry weight basis), and N concentrations (as total N and nitrates) of leaves were not influenced by both biostimulant treatments.ConclusionThe use of plant biostimulants could be a valuable and sustainable strategy to improve the microbiological quality of leafy greens to produce ready-to-eat foods.